The Parenting Style of Ustadz in Enhancing Students' Academic Achievement at Al Azizah Islamic Boarding School, Karanggeneng Godong Grobogan, Academic Year 2023/2024 - Azis, M. Abdul; Santoso, Rochmat Budi (Jurnal Indonesia Sosial Sains, 2024)
This research aims to determine: (1) The approach of ustadz parenting in improving the learning achievement of students at Al Azizah Islamic Boarding School Karanggeneng Godong Grobogan in the 2023/2024 school year (2) The method of ustadz in improving the learning achievement of students at Al Azizah Islamic Boarding School Karanggeneng Godong Grobogan in the 2023/2024 school year (3) The evaluation carried out by ustadz in improving the learning achievement of students at Al Azizah Islamic Boarding School Karanggeneng Godong Grobogan in the 2023/2024 school year. This research uses a qualitative type, where data is obtained by observation, interviews and documentation, the data that has been collected is analyzed through the data stages so that the data obtained data on the implications of the implementation of ustadz parenting patterns in improving learning achievement at the Al Azizah Karanggeneng Godong Grobogan Islamic Boarding School in the 2023/2024 school year. The results showed that: (1) The approach of ustadz parenting in improving the learning achievement of students at Al Azizah Karanggeneng Godong Grobogan Islamic Boarding School in the 2023/2024 academic year, the approaches taken by ustadz include through individual approaches, social approaches, task approaches, edutaiment approaches. (2) The ustadz method in improving the learning achievement of students at the Al Azizah Islamic Boarding School Karanggeneng Godong Grobogan in the 2023/2024 school year methods implemented such as: the syawir method, sorogan method, memorization method, habituation method, bandongan method, khitabah method, group study. (3) The evaluation carried out in improving the learning achievement of students at the Al Azizah Islamic Boarding School Karanggeneng Godong Grobogan in the 2023/2024 school year measures students with tests can be divided into three types, among others: 1) formative tests 2) summative tests 3) diagnostic tests .